THE INFLUENCE OF GRAVITY COEFFICIENT ON THE STRUCTURE OF CENTRIFUGAL CASTINGS SILUMINA AK18 - V. Yu. Stecenko; K. N. Baranov; V. V. Novikov (Литьë и металлургия)
Influence of the gravity coefficient value on structure and extent of allowance zone on machining of castings with diameter of 135 mm from AK18 alloy is investigated. It is established that optimum value of gravity coefficient makes 120–140.